-2x+7=-5x+6x+10

Simple and best practice solution for -2x+7=-5x+6x+10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2x+7=-5x+6x+10 equation:


Simplifying
-2x + 7 = -5x + 6x + 10

Reorder the terms:
7 + -2x = -5x + 6x + 10

Reorder the terms:
7 + -2x = 10 + -5x + 6x

Combine like terms: -5x + 6x = 1x
7 + -2x = 10 + 1x

Solving
7 + -2x = 10 + 1x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
7 + -2x + -1x = 10 + 1x + -1x

Combine like terms: -2x + -1x = -3x
7 + -3x = 10 + 1x + -1x

Combine like terms: 1x + -1x = 0
7 + -3x = 10 + 0
7 + -3x = 10

Add '-7' to each side of the equation.
7 + -7 + -3x = 10 + -7

Combine like terms: 7 + -7 = 0
0 + -3x = 10 + -7
-3x = 10 + -7

Combine like terms: 10 + -7 = 3
-3x = 3

Divide each side by '-3'.
x = -1

Simplifying
x = -1

See similar equations:

| 16m^2=8m*10m | | 2(x-4)=x+4 | | 6=(-x-3) | | 2x^2-6x+32=0 | | A=a+(n-1)(d) | | -4+r= | | 14=10x+4 | | 2x-8y-6=0 | | 4d+18+9d= | | (2x-3)-(4x-5)=6y | | 7(x-4.5)=2.8 | | -4+r+20= | | t*2-1= | | n(3n+2)=1 | | x^8-15x^7-16x^6= | | 27a^3+8b^3=0 | | 17+11r+15m-2r-4m-16= | | 4x-1+x+15=180 | | 6x-7.80=97.20 | | 4x=16+3x | | 7+11x-4=7x+59-4x | | -4x-7=-5x-1 | | -12y-10=-by+14 | | 15x+8y+1z=90 | | X-2+5x= | | (3x)(3x)-2x-1=0 | | 4+0+n= | | 8x-9+5=7x+3 | | 6x-13-2x=6x-8 | | 6[1-n]=-6n+1 | | 82=7(x+6)-2 | | -x^2-7x+196=0 |

Equations solver categories